Electrochemical sensing of Ni2+ on Screen-Printed Carbon Electrodes (SPCEs) by exploiting the chelating and sequestering abilities of the natural polyphenolic compound morin - Abate, Chiara; Presti, Alessandro Lo; Giuffrè, Ottavia; Foti, Claudia (Microchemical journal, 2025)
[Display omitted] •Determination of the formation constants of the system Ni2+-morin.•Determination of the sequestering abilities of morin toward Ni2+.•Exploration of the electrochemical behavior of morin by CV.•Development of a simple electrochemical procedure for the detection of Ni2+.•Good analytical performance of the system Ni2+-morin. The research aimed to develop an alternative strategy for the selective detection of Ni2+ in aqueous solution, exploring the chelating and sequestering properties of a natural polyphenolic ligand, morin (MRN, L5−). To this end, the formation constant values of Ni2+-MRN species (in NaCl aqueous solutions, at I/mol L−1 = 0.15 and T/K = 298.15) were determined to evaluate the sequestering abilities of MRN toward Ni2+ under different pH conditions (2.0 ≤ pH ≤ 9.0). In this pH range, Cyclic Voltammetry (CV) experiments were conducted on MRN, without and in the presence of Ni2+. In both cases, the peak anodic current (ipa) of MRN was higher at pH 7.3. Therefore, the binding ability of the ligand was exploited to electrochemically detect Ni2+ by performing titrations of MRN solutions with Ni2+ in Britton-Robinson (BR) buffer (pH 7.3) using Different Pulse Voltammetry (DPV). The linear concentration range was found to be: 0.5 ≤ [Ni2+]/nmol L−1 ≤ 9.3, with Limit of Detection (LOD) and Limit of Quantification (LOQ) values of 0.21 nmol L−1 and 0.71 nmol L−1, respectively. The stability, repeatability, reproducibility and selectivity of the system Ni2+-MRN were also defined. For the study of selectivity, Ca2+, Mg2+, Mn2+, Fe2+, Co2+, Cu2+ and Zn2+, up to a 100-fold concentration, were taken into account.